Analisis Hubungan Pengalaman PKL dan Kemampuan Akademis Siswa terhadap Kesiapan Kerja Siswa SMK : Studi Meta Analisis - Muhammad Maulana Syahputra; Arif Boy Wilson; Safrinanda Harahap; Nizwardi Jalinus; Fadhilah Fadhilah (Departement of Mathematics Education, 2023)
Vocational High School (SMK) education, graduates are expected to be ready to enter the world of work. There are problems that cannot be fulfilled, especially in the world of work industry, so that unemployment is increasing. At least the ability of students in the academic field on the work readiness of vocational students. The method used is meta-analysis which collects primary research data from seven sources of articles. This study uses correlation analysis consisting of effect size and summary effect to measure the research hypothesis. The result is that the accepted hypothesis is z = 8.378, p <0.001, 95% CI 0.482 and 0.777 with a positive correlation coefficient of 0.629 in the high category.